THE EFFECT OF COMPANY SIZE, LEVERAGE, PROFITABILITY AND DIVIDEND POLICY ON COMPANY VALUE ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2014-2018 PERIOD - Alfiatul Maulida; Maria Evania Karak (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The main goals of the company is to maximize the prosperity of stakeholders. This goals can be achieved by maximizing the value of company. Sometimes, the company failed to increase the value of the company. One of the causes the company inadequacy inadequacy in applying the factors that affectfirm value. This causes the company’s performance to be viewed poorly by its stakeholders. The purpose of this study was conducted to determine the effect of variable company size, leverage, profitability, and dividend to policy on firm value in manufacturing companies listed on the BEI 2014-2018 period. The sample of this research is manufacturing companies listed on the BEI in the 2014-2018 period with a total of 8 companies and using the purposive sampling method, while the data analysis technique uses multiple regression analysis which is supported by the classical assumption test is normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The result of this study indicate that testing the effect of firm size, leverage, profitability, simultaneously on firm value obtained significant result, partially, dividend policy does not have a significant efeect on firm value.